Vulnerability of algae and seagrasses to climate change - Mannino, AM; Graziano, M; Toccaceli, M (country:AL, 2012)
Biodiversity is undergoing rapid and worrying changes, partially driven by anthropogenic activities. Human impacts and climate change (e.g. increasing temperature and ocean acidification) represent the most serious threats to biodiversity and ecosystem functioning. Aim of this study was to assess, analysing the scientific literature and published data, how climate change can affect algae and seagrasses, evaluating their vulnerability and the possibility to use these organisms as indicators. Algae and seagrasses have a central role for several important ecological processes in aquatic ecosystems, and their loss can lead repercussions for the ecological function. Climate stressors affected acquatic vegetation, acting both in isolation and in combination with local perturbations (e.g. nutrient enrichment), reducing the resilience of marine communities. Ocean acidification has negative effects on calcification rates of calcareous algae; sea warming affects both the stability of Posidonia oceanica meadows and their potential recolonization. Considering future climate scenario researchers and policy makers have to plan measures to preserve biodiversity and the status of health of the marine ecosystems.